Differences in monocyte subsets are associated with short‐term survival in patients with septic shock - Hortová‐Kohoutková, Marcela (J Cell Mol Med, 2020)
Sepsis is characterized by dynamic changes of the immune system resulting in deregulated inflammation and failure of homoeostasis and can escalate to septic shock. Circulating monocytes and other innate immune cells are among the first ones to recognize and clear pathogens. Monocytes have an important role in sepsis and septic shock and have been studied as potential diagnostic markers. In total, forty‐two patients with septic shock were recruited and blood samples obtained within first 12 hours of ICU admission. We showed that frequency of classical and intermediate monocytes assessed at the time of admission to the intensive care unit are significantly distinct in patients with septic shock who survived longer that five days from those who died. These parameters correlate significantly with differences in serum levels of inflammatory cytokines MCP‐1, IL‐6, IL‐8, IL‐10, and IL‐18, and with the proportion of helper and cytotoxic T cells. The described changes in frequency of monocyte subsets and their activation status may predict short‐term septic shock survival and help with fast identification of the group of vulnerable patients, who may profit from tailored therapy.